2006
DOI: 10.1089/neu.2006.23.1632
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Locomotor Recovery following Spinal Cord Contusion in Adult Rats

Abstract: Injury to the spinal cord not only disrupts the functioning of spinal circuits at the site of the impact, but also limits sensorimotor function caudal to the level of the lesion. Ratings of gross locomotor skill are generally used to quantify locomotor recovery following spinal cord injury (SCI). The purpose of this study was to assess behavioral recovery following SCI with three tasks: (1) BBB ratings, (2) walking on a horizontal ladder, and (3) footprint analyses. Behavioral testing was conducted for 6 posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 58 publications
7
45
0
Order By: Relevance
“…Further investigations reported that spared white matter volume is the parameter correlating with functional outcome the most (McEwen and Springer, 2006;Schucht et al, 2002;You et al, 2003). This also holds true for mice of different genetic backgrounds (Hashimoto et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Further investigations reported that spared white matter volume is the parameter correlating with functional outcome the most (McEwen and Springer, 2006;Schucht et al, 2002;You et al, 2003). This also holds true for mice of different genetic backgrounds (Hashimoto et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, no study has been conducted to provide a detailed description of the foot progression during the step cycle in normal and spinal injured rodents. Through foot print analysis the foot rotation angle has been extensively applied during overground walking after spinal cord lesions (McEwen and Springer, 2006;Metz et al, 2000b). However, a continuous presentation of the entire time plot of the foot rotation angle instead of a selected point of the stance phase of walking is critical for a detailed gait assessment.…”
Section: Discussionmentioning
confidence: 99%
“…It greatly increases the number and complexity of experimental outcomes that can be simultaneously gathered and potentially minimizes investigator time and effort while increasing throughput in data gathering. Many approaches, including the use of contact electrodes, 3 robotic gait analysis devices, 4 and digital footprint analysis, 5 have been used to automate gait analysis to avoid potential observer bias or limitations. Video-based approaches, such as three-dimensional video analysis 8 and CatWalkÔ, [9][10][11][12] can improve the scope and details of data gathered, but as with BBB scoring, are limited to the gait speed at which the animal chooses to locomote.…”
Section: Introductionmentioning
confidence: 99%